Managing Value Added Tax Issues in Indonesian Business Entities post-IFRS 15 Adoption - Saptono, Prianto Budi; Khozen, Ismail (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2022)
This study analyzes challenges related to value-added tax (VAT) transactions in Indonesia following the convergence of International Financial Reporting Standards 15 (IFRS 15) into Statements of Financial Accounting Standards 72 (SFAS or "PSAK" 72). This study took a qualitative method, combining document abstraction from the literature with in-depth interviews with key informants selected purposively. This study provides an overview of the characteristics of transfer of control under PSAK 72 and the time of supply under the VAT Law. It is unavoidable that the two approaches go different paths. This study suggests that businesses in Indonesia revise the contract terms with customers to contain explicit clauses regarding the time of supply in order to alleviate incompatibilities between the two approaches. It also encourages that new contracts with customers incorporate and ensure the inclusion of each party's VAT obligations. Due to the lack of a uniform standard for commercial interests and tax administration, business entities should undertake the initiative to ensure legal certainty through contractual arrangements by containing adequate information for tax purposes. The significance of this work lies in its attempt to reconcile the accounting and taxation distinctions using an Indonesian context as a lens. Although the implementation of tax law varies according to jurisdiction, the notion of time of supply is applied universally, making this study important as a precedent for situations in other countries.